The Changing Landscape of Spanish Language Curricula : Designing Higher Education Programs for Diverse Students - Brown, Alan V.; Thompson, Gregory L. (College teacher) (Book collections on Project MUSE., 2018)
As Spanish language study grows, the field seems to be in the midst of a curricular identity crisis. During this growth, Spanish has become a second, rather than a foreign, language in the US. This leads to unique opportunities and challenges for curriculum and syllabus design, materials development, individual and program assessment, and classroom pedagogy. In their book, Brown and Thompson try to address the challenges with each of these topics and propose ideas for development and further study. This book will provide a must-read in-depth analysis of the state of Spanish postsecondary education by presenting unique data that reflect the growth and change of Spanish programs in the US, and by critically reflecting on what issues may ensue and how to deal with them. They worked with data from the College Board and ETS, and conducted their own survey of almost 700 Spanish language educators and present it here. Connecting social, linguistic, and pedagogical trends in contemporary Spanish language education to programmatic and curricular innovation at the postsecondary level is the driving force behind this book. Among the topics they will address are: Heritage learners, service learning, Spanish for specific purposes, assessment, Spanish-speaking community context, teacher training, online and hybrid teaching, and the idea of national standards.